2019
DOI: 10.1167/iovs.19-27704
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA PVT1 Silencing Prevents the Development of Uveal Melanoma by Impairing MicroRNA-17-3p–Dependent MDM2 Upregulation

Abstract: PURPOSE. Uveal melanoma is a common primary intraocular malignancy accompanied by high mortality. Previous evidence has highlighted the implication of microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) in uveal melanoma. Accordingly, we further uncovered the possible role of lncRNA plasmacytoma variant translocation 1 gene (PVT1) and microRNA-17-3p (miR-17-3p) in uveal melanoma. METHODS. A series of experiments were performed to examine the relationship among lncRNA PVT1, miR-17-3p, and murine double minute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Several in vitro studies demonstrated that lncRNAs played a role in UM tumorigenesis. The lncRNA PVT1 (Plasmacytoma variant translocation 1 gene) was found to be overexpressed in tissue biopsy of 28 UM patients [71]. This finding was consistent with those of Xu et al, who investigated the expression of lncRNA PVT1 by using deep-RNA sequencing data from the UM Cancer Genome Atlas.…”
Section: Main Clinical Findingssupporting
confidence: 87%
“…Several in vitro studies demonstrated that lncRNAs played a role in UM tumorigenesis. The lncRNA PVT1 (Plasmacytoma variant translocation 1 gene) was found to be overexpressed in tissue biopsy of 28 UM patients [71]. This finding was consistent with those of Xu et al, who investigated the expression of lncRNA PVT1 by using deep-RNA sequencing data from the UM Cancer Genome Atlas.…”
Section: Main Clinical Findingssupporting
confidence: 87%
“…[36][37][38] Wu et al indicated that PVT1 silencing could prevent the development of uveal melanoma through impairing miR-17-3p-dependent MDM2 upregulation. 39 Furthermore, PVT1 could modulate the proliferation and apoptosis of lens epithelial cells in diabetic cataract through regulation miR-214-3p/MMP2 axis. 30 Besides, it has been previously reported that miR-181a-5p could mediate the progression of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of lncRNA PVT1 (Chr 8q24.21) were found to be considerably higher in UM compared to normal tissues [ 21 , 90 ]. It has an oncogenic function in the initiation and development of metastasis of various neoplasms, including UM [ 96 , 97 , 98 , 99 ].…”
Section: Long Non-coding Rnas In Ummentioning
confidence: 99%
“…It has an oncogenic function in the initiation and development of metastasis of various neoplasms, including UM [ 96 , 97 , 98 , 99 ]. The silencing of PVT1 impedes the biological functions of UM cells, resulting in the inhibition of proliferation, S-phase sequestration, and migration in addition to inducing apoptosis [ 21 ].…”
Section: Long Non-coding Rnas In Ummentioning
confidence: 99%
See 1 more Smart Citation